2008
DOI: 10.1038/nm.f.1895
|View full text |Cite
|
Sign up to set email alerts
|

The biology of infertility: research advances and clinical challenges

Abstract: Reproduction is required for the survival of all mammalian species, and thousands of essential ‘sex’ genes are conserved through evolution. Basic research helps to define these genes and the mechanisms responsible for the development, function and regulation of the male and female reproductive systems. However, many infertile couples continue to be labeled with the diagnosis of idiopathic infertility or given descriptive diagnoses that do not provide a cause for their defect. For other individuals with a known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
687
1
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 841 publications
(709 citation statements)
references
References 233 publications
3
687
1
18
Order By: Relevance
“…Correlations of genes previously identified to be associated with ovarian disease [3441] (Supplemental Table S13) with the transgenerational granulosa cell genes of this study identified a number of genes associated with ovarian disease, Figure 11 and Supplemental Table S14. A gene that was present in the DDT and vinclozolin DMR associated genes and ovarian disease associated genes was Pkp4, plakophilins 4 [34,55].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Correlations of genes previously identified to be associated with ovarian disease [3441] (Supplemental Table S13) with the transgenerational granulosa cell genes of this study identified a number of genes associated with ovarian disease, Figure 11 and Supplemental Table S14. A gene that was present in the DDT and vinclozolin DMR associated genes and ovarian disease associated genes was Pkp4, plakophilins 4 [34,55].…”
Section: Discussionmentioning
confidence: 79%
“…Extensive reviews previously published have summarized the genes that have been associated with ovarian disease [3441]. These published ovarian disease-associated genes were compiled into a list of 416 genes that are listed in Supplemental Table S13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic causes of azoospermia include chromosomal abnormalities, Y chromosome microdeletions, and specific mutations or deletions of several Y chromosomal genes 2, 3. Thus, in 1995, it was demonstrated that DAZ mutations (Yq11.23) cause various forms of human male infertility that range from oligospermia to azoospermia 4, 5. In 1997, it was reported that RBMY (Yq11.223) mutations cause azoospermia via meiotic arrest5, 6 and, in 1999, it was shown that USP9Y (Yq11.2) mutations lead to azoospermia that is secondary to hypospermatogenesis 5, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in 1995, it was demonstrated that DAZ mutations (Yq11.23) cause various forms of human male infertility that range from oligospermia to azoospermia 4, 5. In 1997, it was reported that RBMY (Yq11.223) mutations cause azoospermia via meiotic arrest5, 6 and, in 1999, it was shown that USP9Y (Yq11.2) mutations lead to azoospermia that is secondary to hypospermatogenesis 5, 7. The azoospermia factor (AZF) region on the Y chromosome is one of the most intensively studied regions in male infertility 8, 9.…”
Section: Introductionmentioning
confidence: 99%